Co-targeting RNA Polymerases IV and V Promotes Efficient De Novo DNA Methylation in Arabidopsis - Gallego-Bartolomé, Javier; Liu, Wanlu; Kuo, Peggy Hsuanyu; Feng, Suhua; Ghoshal, Basudev; Gardiner, Jason; Zhao, Jenny Miao-Chi; Park, Soo Young; Chory, Joanne; Jacobsen, Steven E. (Cell, 2019)
The RNA-directed DNA methylation (RdDM) pathway in plants controls gene expression via cytosine DNA methylation. The ability to manipulate RdDM would shed light on the mechanisms and applications of DNA methylation to control gene expression. Here, we identified diverse RdDM proteins that are capable of targeting methylation and silencing in Arabidopsis when tethered to an artificial zinc finger (ZF-RdDM). We studied their order of action within the RdDM pathway by testing their ability to target methylation in different mutants. We also evaluated ectopic siRNA biogenesis, RNA polymerase V (Pol V) recruitment, targeted DNA methylation, and gene-expression changes at thousands of ZF-RdDM targets. We found that co-targeting both arms of the RdDM pathway, siRNA biogenesis and Pol V recruitment, dramatically enhanced targeted methylation. This work defines how RdDM components establish DNA methylation and enables new strategies for epigenetic gene regulation via targeted DNA methylation. [Display omitted] •A panel of RdDM factors can target DNA methylation when fused to an artificial ZF•ZF-RdDM fusions in different mutant backgrounds reveal RdDM hierarchy of action•MORC6 can target DNA methylation•Co-targeting of Pol IV and Pol V synergistically enhances DNA methylation targeting Comprehensive investigation into the genetic pathway of RNA-directed DNA methylation in Arabidopsis defines epistatic relationships and allows for efficient manipulation of DNA methylation to specifically modify developmental phenotypes.